2019
DOI: 10.1038/s41598-019-43275-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in HIV plus dengue coinfection associates with reduced inflammation and milder dengue illness

Abstract: HIV-infected subjects under virological control still exhibit a persistent proinflammatory state. Thus, chronic HIV infection changes the host homeostasis towards an adapted immune response that may affect the outcome of coinfections. However, little is known about the impact of HIV infection on inflammatory amplification and clinical presentation in dengue. Platelets have been shown to participate in immune response in dengue and HIV. We hypothesized that altered platelet responses in HIV-infected subjects ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 90 publications
0
15
0
4
Order By: Relevance
“… 14 , 22 , 27 , 28 Our group and others have previously shown that platelet activation and platelet-leukocyte interactions participate in the pathophysiology of viral infections, including dengue, HIV, and influenza. 20 , 29 - 35 Our central hypothesis is that platelet activation and platelet-monocyte aggregate formation participate in thromboinflammatory responses during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 22 , 27 , 28 Our group and others have previously shown that platelet activation and platelet-leukocyte interactions participate in the pathophysiology of viral infections, including dengue, HIV, and influenza. 20 , 29 - 35 Our central hypothesis is that platelet activation and platelet-monocyte aggregate formation participate in thromboinflammatory responses during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our study, Fas/CD95 expression on T cells were not significantly different in patients receiving ART and degree of Fas/CD95-expressing lymphocytes was comparable between GBV-C co-infected and GBV-C infected 39 . A recent study demonstrated that apoptosis of platelets were similar between DENV infected and coinfected with HIV as evidenced by phosphatidylserine exposure, mitochondrial membrane potential and caspase -9 activation 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Corroborating, the present data demonstrated that most coinfected patients had mild symptons confirming our previous data 14 . More recently, Hotzz et.al., reported that DENV infection in ART-treated HIV patients was associated with reduced vascular instability and liver damage 26 . However, coinfected patients could have severe dengue outcomes 27 .…”
Section: Discussionmentioning
confidence: 99%
“…4A). Of note, increased platelet activation with the exhaustion of α‐granule chemokines is associated with high viral load and immune suppression in AIDS patients, 263 and persists in HIV‐infected subjects under virologic control 264,265 …”
Section: Platelet Innate Immune Receptors In Infectious Diseasesmentioning
confidence: 99%
“…Of note, increased platelet activation with the exhaustion of -granule chemokines is associated with high viral load and immune suppression in AIDS patients, 263 and persists in HIV-infected subjects under virologic control. 264,265 Increased levels of platelet-derived sCD40L participate in HIVassociated neuroinflammation by inducing platelet-monocyte aggregation and infiltration through the blood-brain barrier (Fig. 4A).…”
Section: See the Text For Details And Referencesmentioning
confidence: 99%